Pengaruh Standar Halal Kualitas Produk Dan Kualitas Layanan BMT BRS Yogyakarta Terhadap Tingkat Kepuasan Pelanggan - Tyas, Irlanita Ayuning; Choiri, Ahmad; Nur Azizah, Siti (ITB AAS INDONESIA Surakarta, 2024)
The development of cooperatives in Indonesia is now on the rise but the increase is not followed by the number of members participating. While micro-Sharia financial institutions such as BMT or baitul mal and baitul tamwil are present as a sharia-based financial institution whose purpose is to help the problems of small communities. The development of the amount of performance can be measured through the performance of the enterprise through the level of customer satisfaction. The purpose of this investigation is to know the quality of the products and services of BMT Bangun Rakyat Sejahtera Yogyakarta against customer satisfaction. This research uses a quantitative research method with the analytical technique used is SPSS. This research obtains results that the quality of products and services affects customer satisfaction. This is in line with the TMQ or Total Quality Management theory on the focus of customer satisfaction by optimizing competitiveness through the quality of products and services will have an impact on business performance.